PROTEIN MARKERS, MORPHOLOGICAL AND BREEDING-ORIENTED CHARACTERS IN DUPLICATE ACCESSION IDENTIFICATION IN THE VIR (RUSSIA) AND NORDGEN (SWEDEN) CULTIVATED OAT COLLECTIONS - I. N. Perchuk; A. V. Konarev; I. G. Loskutov; E. V. Blinova; L. Y. Novikova; V. I. Horeva; A. . Kolodinska-Brantestam (Труды по прикладной ботанике, генетике и селекции, 2018)
Methods for identification of duplicate accessions in genebanks and the term “duplicate accession” are discussed. The results of comparative field and laboratory analysis of 112 pairs of potential duplicate accessions from the oat collections of VIR and NordGen are presented. The revealed conformity between the results of the field and laboratory tests proves the use of avenin electrophoretic banding patterns for duplicate identification in the oat collections before field testing or in case of loss of germination in the seeds of the tested accessions.